Analisis Usaha Agroindustri Rengginang Ubi Di Desa Tanah Datar Kecamatan Rengat Barat Kabupaten Indragiri Hulu - Khairudin (CV Edujavare Publishing, 2024)
Cassava rengginang agroindustry in its development is still constrained by several factors, such as limited raw materials, technology and capital as well as fluctuating selling prices. Therefore, it is necessary to study 1). How is the production process carried out 2). How much is the cost, income and efficiency of the agroindustry and 3). How much added value is obtained. Based on the formulation of the problem, the objectives of the study are; 1). Knowing the production process of cassava rengginang 2). Analyzing costs, income and efficiency and 3). Analyzing added value. The study used a case study method on the Labib Al Fitrah Cassava Rengginang agroindustry. The determination of the research location was carried out intentionally (Purposive Sampling) namely in Tanah Datar Village, West Rengat District. The results of the study showed that 1). The production process of Cassava Rengginang agroindustry consists of procurement of cassava raw materials, peeling, washing, grating, pressing, kneading, molding, steaming, drying, frying and packaging until the product is ready to be marketed and consumed. 2). The total cost incurred for each production process is Rp. 748,634, - the highest cost in the cassava rengginang agro-industry business is the labor cost which is Rp. 287,200, - / process (38.36%). The gross income of the Cassava Rengginang agro-industry business is Rp. 800,000, - / production process, net income Rp. 51,366, - / production process. Then the family income is Rp. 355,500, - and the RCR is 1.07 and the added value is Rp. 8,887.50 / Kg after being converted into Cassava Rengginang